2006
DOI: 10.1111/j.1472-765x.2005.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of faecal Escherichia coli from humans and animals by multiple antibiotic resistance analysis

Abstract: Aims:  Multiple antibiotic resistance (MAR) was performed on 128 Escherichia coli isolates, recovered from faecal samples of humans and animals (cattle, goat, sheep) to determine and compare their antibiotic resistance patterns and to evaluate them statistically in order to specify the source of the faecal material. Methods and Results:  Disk diffusion method was applied with a selection of antibiotics. Statistical approach was performed with hierarchical cluster analysis (CA), discriminant analysis (DA) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Kaspar et al (1990) noticed that indexing the antibiotic resistance among E. coli may be useful to identify the sources of faecal contamination in water. Recently, Vantarakis et al, (2006) have observed that MAR analysis is useful tool in differentiating the faecal E.coli from human being and animals.…”
Section: Resultsmentioning
confidence: 99%
“…Kaspar et al (1990) noticed that indexing the antibiotic resistance among E. coli may be useful to identify the sources of faecal contamination in water. Recently, Vantarakis et al, (2006) have observed that MAR analysis is useful tool in differentiating the faecal E.coli from human being and animals.…”
Section: Resultsmentioning
confidence: 99%
“…The aquatic environment can thus be considered a secondary habitat, where some authors have even shown the possible growth of E. coli [17,18]. The diversity of E. coli populations in their secondary habitats has been studied by analyzing the sequences of the gene uidA [19,20], palindromic repetitive sequences [21,22], ribotypes [23], and profiles of antibiotic resistance [24,25]. Using these methods, the dynamics of E. coli populations have been investigated and, in some cases, it has been possible to discriminate between the human or animal origin of the contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The overall inadequate performance of the methods involved resurrected previous concerns of temporal instability of strains within host organisms (Jenkins et al, 2003). Therefore in this study, once the library size was increased to 200 isolates, comparable to numbers frequently reported in several publications (Dombek et al, 2000; Guan et al, 2002; Seurinck et al, 2003; Lasalde et al, 2005; Duran et al, 2006; Vantarakis et al, 2006), a VS of isolates (collected simultaneously, but from different fecal samples) were fingerprinted to serve as an additional means of predicting the classification ability of the known‐source library. In library‐based MST methods, small libraries typically produce high ARCCs solely due to the random placement of isolates into defined categories (Whitlock et al, 2002).…”
Section: Discussionmentioning
confidence: 94%